Normal reference ranges for aortic diameters in preterm infants - Abushaban, Lulu (J Saudi Heart Assoc, 2018)
OBJECTIVE: To establish normal reference ranges and Z-scores for aortic diameters in preterm infants according to the body surface area and assess their correlation with body weight, body surface area, and gestational age. PATIENTS AND METHODS: In a prospective study, 268 preterm infants who fulfilled the criteria for inclusion were examined. Echocardiograms were performed to measure the ascending aorta, transverse aorta, and aortic isthmus diameters on 0 days to 6 days of life and at weekly intervals until the babies reached 36 weeks. Body surface area was divided into 13 groups from 0.07 m(2) to 0.19 m(2). RESULTS: The mean gestational age was 29.8 [± 2.38 standard deviation (SD)] weeks, ranging from 24 weeks to 35 weeks. The mean body weight was 1479 (± 413 SD) g, ranging from 588 g to 3380 g, and the mean body surface area was 0.13 m(2), ranging from 0.07 m(2) to 0.19 m(2). All the aortic diameters correlated well with both body weight and body surface area. Reference ranges with the mean ± SD, range, and Z-scores were calculated for aortic diameters according to the body surface area. A significant gradual increase was observed in ascending aorta, transverse aorta, and aortic isthmus diameters with increasing body surface area. Overall, a progressive and significant increase in ascending aorta, transverse aorta, and aortic isthmus diameters was observed during the first 9 weeks of life. CONCLUSION: The ascending aorta, transverse aorta, and aortic isthmus diameters exhibited a significant correlation with the body surface area and body weight. This study provides reference data with Z-scores that can be used as a normal reference tool for the ascending aorta, transverse aorta, and aortic isthmus diameters for preterm infants based on the body surface area.